Search for neutral heavy leptons produced in Z decays - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andreazza, A; Andrieux, M; et al. (1997)
Weak isosinglet Neutral Heavy Leptons (νm) have been searched for using data collected by the DELPHI detector corresponding to 3.3 × 106 hadronic Z0 decays at LEP1. Four separate searches have been performed, for short-lived νm production giving monojet or acollinear jet topologies, and for long-lived νm giving detectable secondary vertices or calorimeter clusters. No indication of the existence of these particles has been found, leading to an upper limit for the branching ratio BR(Z0 → νmν̄) of about 1.3 × 10-6 at 95% confidence level for νm masses between 3.5 and 50 GeV/c2. Outside this range the limit weakens rapidly with the νm mass. The results are also interpreted in terms of limits for the single production of excited neutrinos. © Springer-Verlag 1997.